Incidence, Inequality and Determinants of Catastrophic Health Expenditure in India - Rohin Gaddam; K. Ramachandra Rao (Journal of Health Management, 2023)
This study tries to estimate the incidence, intensity and inequality of Catastrophic Health Expenditure in India and its determinants using unit-level data from the four consecutive surveys of NSSO on ‘Healthcare Consumption and Morbidity’ spread across a 23-year period.
Keywords: Health Expenditure; NSSO